Spatial Dynamics of Urbanization: Analyzing the Impact on Amathus Archaeological Landscape - Leventis, Georgios; Argyriou, Athanasios V.; Abate, Dante; Hadjimitsis, Diofantos G. (My University, 2024)
This study uses advanced spatial analysis and geoinformatics to evaluate how urbanization affects archaeological sites. The research focuses on Amathus in Cyprus. Using data cube, remote sensing, and GIS, the study examines environmental changes, particularly vegetation patterns, around the site. Techniques such as Principal Component Analysis and Pearson correlation uncover a moderate positive relationship between changes in the Normalized Difference Vegetation Index and urban development. The study also investigates the spatial connection between urban structures and the archaeological site within 100 and 300-meter buffer zones. Emphasizing the importance of geospatial technologies in assessing and managing cultural heritage risks, the research highlights their role in real-time monitoring and developing predictive models. This approach is crucial for comprehending and mitigating the effects of urban expansion on heritage sites, advocating for the integration of these methodologies in heritage management.
Keywords: Normalized difference vegetation index; Satellites; Urban areas; Vegetation mapping; Predictive models; Real-time systems; Cultural differences